Mechanical response of galvanised steel sandwich structure with different numbers of web core and different spacing distance of web plate under bending load - Romli, N. K.; Rejab, M. R. M.; Jiang, X. X.; Soffie, S. M.; Ishak, M. (Faculty Mechanical Engineering, UMP, 2022)
Sandwich structures are widely used in a variety of industrial applications due to their ability to provide high bending stiffness while remaining lightweight. The deformation of this structure and its relation to the stiffness of the galvanized steel is investigated. A series of three-point bending response and subsequent failure modes in web-core laser-welded sandwich structure based on galvanised steel is also investigated. The web-core sandwich structure was manufactured using fibre laser welding technique to joint face and web plates perpendicularly to produce a range of lightweight sandwich structure. The role of the number of cores and spacing distance were purposed to determine the overall deformation of global deflection behaviour of the sandwich structure. The results were compared, and it is showed that the acted load produced bending on faceplate and caused debonding at weld joint (between faceplate and web plate). The continued bending was also caused debonding between PVC foam and adjacent plate. Subsequently, load-displacement trace was used as evidence of the comparison, where seven cores with 20 mm spacing distance exhibited higher force, approximately 1.091 kN. The three-point bending test results indicated that the higher number of cores possessed better performance in bending strength. The effect of the spacing distance of web plates in sandwich structure was also examined. In five cores specimen, it is showed that as the spacing distance decreased, the bending strength increased, where bending stiffness value of 18 mm (0.313 kN/mm) is higher than 19 mm (0.288 kN/mm) and 20 mm (0.281 kN/mm). The effectiveness of the sandwich structure depended on the optimal design as to achieve lightweight and its bending strength.